2020
DOI: 10.1016/j.smallrumres.2020.106192
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Tunisian sheep breeds as inferred from genome-wide SNP markers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
7
9
0
Order By: Relevance
“…Past and recent human-mediated translocations and dispersal of the two breeds across Tunisia has brought the two breeds in close geographic proximity [57] and is resulting in cross-mating that is homogenizing their genomes. A similar nding was reported by [52]. The fact that the genomes of the B and Q breeds could not be differentiated by ADMIXTURE in each cluster provides evidence at the genome level that supports past and on-going uncontrolled mating of the fat-tailed Barbarine with thin-tailed breeds to reduce the fat content, especially of the tail, in the Barbarine carcass [58].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Past and recent human-mediated translocations and dispersal of the two breeds across Tunisia has brought the two breeds in close geographic proximity [57] and is resulting in cross-mating that is homogenizing their genomes. A similar nding was reported by [52]. The fact that the genomes of the B and Q breeds could not be differentiated by ADMIXTURE in each cluster provides evidence at the genome level that supports past and on-going uncontrolled mating of the fat-tailed Barbarine with thin-tailed breeds to reduce the fat content, especially of the tail, in the Barbarine carcass [58].…”
Section: Discussionsupporting
confidence: 71%
“…The variability in the four genetic groups revealed by PCA and ADMIXTURE was of the same magnitude as that of the two cohorts. Comparable levels of genetic variability have been reported in Egyptian [50], Algerian [51], Tunisian [52] and Russian [53] breeds of sheep.…”
Section: Discussionmentioning
confidence: 84%
“…Gaouar et al [ 23 ] reported an F ST value of 0.036 for the five major sheep breeds of Morocco, and of 0.038 for six Algerian breeds [ 41 ]. Concerning the Tunisian breeds, the genetic differentiation was even lower, with F ST values of about 1.7% for a set of four breeds [ 39 , 42 ], and 0.021 for a set of six breeds, including one crossed population [ 43 ]. In contrast, higher values were reported for Central and South African [ 44 , 45 ], European [ 46 51 ], and Oriental breeds [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The population differentiation analysis showed a relatively weak population structure between BARB and QFO breeds and their crossed population (CROSS) with the exception of the subpopulation of the BARB group that originated from a prolificacy-based selected flock with significant levels of inbreeding (Lassoued et al, 2017). Moreover, the PCA and admixture results revealed clear differentiation of breeds originating from Europe (THIB and SS) from the remaining populations previously evidenced in genome-wide studies using medium density ovine array (Baazaoui et al, 2021;Bedhiaf-Romdhani et al, 2020). Indeed, this structure was expected because THIB has shown substantial Merino introgression via Merino ancestry to acquire tolerance against white-colored skin photosensitization (Baazaoui et al, 2020), whereas the SS breed is a small population imported into Tunisia by Italians in the early twentieth century to be the only dairy breed in North Africa (Saadoun et al, 2004).…”
Section: Population Stratificationmentioning
confidence: 70%